K'iche' Maya Verbs of Breaking and Cutting - Pye, Clifton (Kansas Working Papers in Linguistics, 1996)
K'iche' Maya divides the breaking and cutting domains into much more specific actions than English or Spanish, e.g., -pi'i:j `break something soft', -joyopi:j `break off a banana'. K'iche' does not have a general word for breaking that can be substituted for the specialized breaking verbs in the way that English `break' can be used to describe more specific senses of picking, popping, smashing or shattering. Thus, K'iche' has gaps in its lexical and conceptual structure with no equivalent lexical or phrasal expressions for English `break' and `cut'. Such facts pose severe difficulties for the notion of a universal conceptual structure underlying language.